Comparison of the systemic vs. local application of Bleomicin in dogs undergoing electrochemotherapy - Salazar-Acuña, Edison Gustavo; Castillo-Hidalgo, Edy; Moran-Obando, Wiliam (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The objective of the present study was to compare the effect of electrochemotherapy (ECT) plus local and systemic bleomycin, in dogs with neoplasms of different cellular origins, which were treated at the “La Primavera” Veterinary Clinic in the City of Quito, Pichincha, Ecuador. There were 10 canine patients (Canis lupus familiaris). The diagnosis was made by histopathology and cytology, the volumetric calculation of the tumor was obtained using the formula to calculate the tumor volume [(a×b×c×(π/6)]. The treatment was based on the administration of bleomycin 15 International Unit per square meter (IU·m2) of body surface, systemic route, and intratumoral infiltration of bleomycin at a dose of 0.25 IU per cubic centimeter (IU·cm3) of tumor surface. Considering the high selectivity of bleomycin for epithelial cells and the characteristics of tumor vascularization, electrical pulses were subsequently applied with an intensity of 1,000 volts per square centimeter (V·cm2), using different types of electrodes. Twenty eight days after the application of the therapy, the tumor masses were reduced by 50%, achieving an objective response to the applied treatment.